2002
DOI: 10.2138/rmg.2002.48.18
|View full text |Cite
|
Sign up to set email alerts
|

Phosphates as Nuclear Waste Forms

Abstract: INTRODUCTIONThe disposal of radioactive "waste" generated by the nuclear fuel cycle is among the most pressing and potentially costly environmental problems of the 21st century, a heritage from the Atomic Age of the 20th century. Proposed disposal strategies are complicated, not only because of the large volumes and activities of waste, but also because of the political and public-policy issues associated with the long times required for containment and disposal (10 4 to 10 6 years). The development and use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
102
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(104 citation statements)
references
References 131 publications
(124 reference statements)
1
102
0
1
Order By: Relevance
“…Amorphous domains are absent, only some misoriented regions interpreted as old ␣-recoil tracks, have been found. Two explanations are possible: (a) either the lattice can heal at such low temperatures, in accordance with experimental data (Meldrum et al, 1996(Meldrum et al, , 1997Ewing and Wang, 2002), or (b) ionization created by ␣-particles, or electrons from ␣-decay in the U and Th decay chains partially anneal structural damages created by the recoil of nuclei (Ouchani et al, 1997;Ewing and Wang, 2002;Harrison et al, 2002). Future experimental studies should focus on the healing mechanisms of monazite.…”
Section: Interpretation Of the Resultssupporting
confidence: 58%
“…Amorphous domains are absent, only some misoriented regions interpreted as old ␣-recoil tracks, have been found. Two explanations are possible: (a) either the lattice can heal at such low temperatures, in accordance with experimental data (Meldrum et al, 1996(Meldrum et al, , 1997Ewing and Wang, 2002), or (b) ionization created by ␣-particles, or electrons from ␣-decay in the U and Th decay chains partially anneal structural damages created by the recoil of nuclei (Ouchani et al, 1997;Ewing and Wang, 2002;Harrison et al, 2002). Future experimental studies should focus on the healing mechanisms of monazite.…”
Section: Interpretation Of the Resultssupporting
confidence: 58%
“…Furthermore, atomic diffusion via a given mechanism is rate limited by the largest activation barrier separating two minimum energy atomic configurations. It is the rate limiting process that will impact upon the suitability of the mineral phase as a potential waste form, where leeching of elements must be minimised [8].…”
Section: Introductionmentioning
confidence: 99%
“…Due to this system's considerable compositional flexibility it is used in a number of applications 2,3 . In particular, it has been observed that a wide range of elements can be accommodated in synthetic and naturally occurring apatites 4,5 . This compositional flexibility is being exploited by the nuclear industry where apatites are being considered as constituents for multi-compound waste forms.…”
Section: Introductionmentioning
confidence: 99%